TINJAUAN PSIKOANALISIS KARYA KOLEKSI TUBUH WANITA PADA KARYA SENI FOTOGRAFI MANRAY - Damarjati, Fx. (Jurnal Industri Kreatif dan Inovatif, 2024)
The research tries to analyze photographs of the work of Man Ray, an artist whose existence was greatly influenced by the emergence of Dadaism in the world of fine arts. Of the many works produced by researchers, researchers are interested in his nude photographs. The nude photos were influenced by his naughtiness as a chest man and his sexual tendencies as a man who wanted to photograph the beauty of the opposite sex, especially since he worked for a famous fashion magazine at that time. This study uses a qualitative method. Sigmund Freud's theory of psychoanalysis as a theoretical basis for analyzing Man Ray's photographic works. Research shows that photographing anything related to sexuality is not what one imagines. Controlling sexual desires becomes a separate individual in achieving a work.